Absence of Charge Transfer State Enables Very Low V-OC Losses in SWCNT:Fullerene Solar Cells - Classen, Andrej; Einsiedler, Lukas; Heumuelier, Thomas; Graf, Arko; Brohmann, Maximilian; Berger, Felix; Kahmann, Simon; Richter, Moses; Matt, Gebhard; Forberich, Karen; Zaumseil, Jana; Brabec, Christoph (Advanced Energy Materials, 2019)
Current state-of-the-art organic solar cells (OSCs) still suffer from high losses of open-circuit voltage (V-OC). Conventional polymer:fullerene solar cells usually exhibit bandgap to V-OC losses greater than 0.8 V. Here a detailed investigation of V-OC is presented for solution-processed OSCs based on (6,5) single-walled carbon nanotube (SWCNT): [6,6]-phenyl-C-71-butyric acid methyl ester active layers. Considering the very small optical bandgap of only 1.22 eV of (6,5) SWCNTs, a high V-OC of 0.59 V leading to a low E-gap/q - V-OC = 0.63 V loss is observed. The low voltage losses are partly due to the lack of a measurable charge transfer state and partly due to the narrow absorption edge of SWCNTs. Consequently, V-OC losses attributed to a broadening of the band edge are very small, resulting in V-OC,V-SQ - V-OC,V-rad = 0.12 V. Interestingly, this loss is mainly caused by minor amounts of SWCNTs with smaller bandgaps as well as (6,5) SWCNT trions, all of which are experimentally well resolved employing Fourier transform photocurrent spectroscopy. In addition, the low losses due to band edge broadening, a very low voltage loss are also found due to nonradiative recombination, Delta V-OC,V-nonrad = 0.26 V, which is exceptional for fullerene-based OSCs.
Keywords: all-carbon absorbers; charge transfer state; organic photovoltaics; single-walled carbon nanotubes; V-OC loss analysis

Revealing Hidden UV Instabilities in Organic Solar Cells by Correlating Device and Material Stability - Classen, Andrej; Heumüller, Thomas; Wabra, Isabell; Gerner, Johannes; He, Yakun; Einsiedler, Lukas; Li, Ning; Matt, Gebhard; Osvet, Andres; Du, Xiaoyan; Hirsch, Andreas; Brabec, Christoph (Advanced Energy Materials, 2019)
With state-of-the-art organic solar cells (OSCs) surpassing 16% efficiency, stability becomes critical for commercialization. In this work, the power of using photoluminescence (PL) measurements on plain films is demonstrated, as well as high-performance liquid chromatography analysis to reveal the origin of UV instabilities in OSCs based on the most commonly used acceptors PC70BM ([6,6]-phenyl-C71-butyric acid methyl ester), ITIC (3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2′,3′-d′]-s-indaceno[1,2-b:5,6-b′]dithiophene), and o-IDTBR (indacenodithiophene-based non-fullerene acceptor). The UV dependent stability tests reveal instabilities in solar cells based on PC70BM and ITIC while devices based on o-IDTBR are highly stable even under UV illumination. The analysis of solar cell devices based on charge extraction and sub-bandgap external quantum efficiency only shows the UV-dependent emergence of traps, while PL spectra of plain films on glass allows the disentanglement and identification of individual instabilities in multi-component bulk-heterojunction devices. In particular, the PL analysis demonstrates UV instabilities of PC70BM and ITIC toward the processing additive 1,8 diiodooctane (DIO). The chemical analysis reveals the in-depth mechanism, by providing direct proof of photochemical reactions of PC70BM and ITIC with UV-induced radicals of DIO. Based on this scientific understanding, it is shown how to stabilize PBQ-QF:PC70BM devices.
CRIS-Team Scopus Importer:2019-09-17
Keywords: degradation; diiodooctane; organic solar cells; stability; UV